Penetapan Talak Bain Kasus Gugat Cerai Khulu’ Perspektif KHI & Ibn Hazm - Arifin, Syukron; Al Amin, Habibi (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
In Islamic law there are differences of opinion among scholars regarding the position of Khulu'. Some scholars are of the opinion that Khulu 'is part of Thalaq and some are of the opinion that it is Fasakh. There is no difference regarding the position of Khulu' according to the Shafi'i Madzhab adopted by KHI with Ibn Hazm, but there are differences of opinion about the status of divorce after the occurrence of Khulu' between Ibn Hazm and Islamic law that applies in Indonesia in this case KHI. Researchers are interested in knowing about the difference in divorce status between KHI and Ibn Hazm. Based on the results of the study, it can be concluded that Ibn Hazam considers khulu' as divorce raj'i while KHI considers khulu' as divorce bain. If it is considered talak raj'i then the husband is allowed to refer to it during the wife's iddah and if that happens then the husband must return all the assets that have been obtained from his wife as ransom. However, if it is considered as talak bain, the husband cannot refer his wife when the wife is in the iddah period and reduces the number of talaqs that the husband has.